Personalising Practice Using Preferences for Meditation Anchor Modality - Anderson, Thomas; Farb, Norman A. S. (Frontiers in Psychology, 2018)
Many people are starting to establish contemplative practices and Mindfulness-Based Interventions have become quite popular. While Mindfulness-Based Interventions positively impact well-being, drop-out and lack of practice-maintenance plagues these interventions. Such adherence issues may reveal a lack of fit between participant partiality for attentional anchors of meditative practice and the intervention's use of the breath as the anchor of attention. No study had yet compared partiality toward practices using anchors from different sensory modalities (e.g. auditory, visual) thus the present study examined such individual differences, sharing resources on the Open Science Framework (osf.io/hcnz2/). Participants (N=82) engaged 10-min practices within three modalities (somatosensory, auditory, visual) and partiality toward these meditations was modelled. Partiality differences did exist: 49% preferred the breath, 30% the auditory-phrase, and 21% the visual-image. Pre-practice motivation and anchor-modality predicted partiality while cardiac responses were also positively associated with partiality. Preferences were updated through experience and over half of participants left the experiment partial to a different anchor than their initial meditation-naïve bias. Tangible next-steps are discussed, including integrating additional anchor modalities into existing interventions by offering brief practices with a variety of anchors. Suggestions are made for increasing post-training contact using email-automation to answer central practice-maintenance questions, including whether and which contemplative benefits are predicated on continued practice.